The association between elder abuse and refrainment from daily activities during the COVID-19 pandemic among older adults in Japan: A cross-sectional study from the Japan Gerontological Evaluation Study - Chie Koga; Taishi Tsuji; Masamichi Hanazato; Koryu Sato; Katsunori Kondo (Elsevier, 2022)
Objectives: Elder abuse is a public health issue that is thought to have increased during the COVID-19 pandemic due to lockdowns and behavioral restrictions. This study examines the association between elder abuse and refrainment from daily activities during the pandemic. Methods: We used data from a self-administered mail survey conducted by the Japan Gerontological Evaluation Study (JAGES) from November 2020 to February 2021 in 11 municipalities. Our participants included 18,263 older adults (age ≥65 years) who were independent in their daily lives. Logistic regression analysis was conducted to evaluate the association between elder abuse and refrainment from 10 daily activities, and the total number of refrained behaviors. Results: Experiences of abuse were reported by 288 participants (1.6%). The risk of elder abuse was 1.37 times (95% confidence interval, 1.04-1.81) higher among those who refrained from shopping for food and daily necessities and 1.60 times (1.20-2.13) higher among those who refrained from interaction with neighbors, than those who did not. Also, a dose-response relationship was observed where the risk of abuse increased with the number of restrictions. Conclusion: The risk of elder abuse increased as the number of refrained behaviors increased which suggests that refrainment from multiple behaviors may significantly increase the risk of elder abuse, compared with refrainment from a single behavior. To avoid increasing the risk of abuse in likely future pandemics, it is necessary to maintain social connections without face-to-face contact, or with adequate infection control measures.